Phytochemical Study of some Flavonoids Present in the Fruits of Two Ammi L. Species Wildly Grown in Iraq - Z. Abdul-Jalil, Thukaa; Saour, Kawkab; Nasser, Abdul- MutalibA. (Iraqi Journal of Pharmaceutical Sciences, 2017)
Ammi species belong to the family Umbellifereae that provide a host of bioactive compounds (mainly coumarins and flavonoids) of important biological activities, like prevention and treatment of heart and vascular disease and some types of cancer. Literature survey revealed that there was no study concerning Ammi flavonoids in Iraq. Ammi majus and Ammi visnaga, which are wildly grown in Iraq, were chosen for this study. This study concerned with extraction, identification, isolation, and purification of some biologically important flavonols quercetin and kaempferol from the fruits of Ammi majus and Ammi visnaga. Extraction of these flavonols was carried out using 85% methanol and 90% ethanol. Identification of these flavonols quercetin and kaempferol was done using thin Layer chromatography (TLC) where different solvent systems had been tried. Ultra violet (UV) Light and iodine vapor where used for detection. This identification was further augmented by using high performance Liquid chromatography (HPLC) and then these flavonols were isolated and purified. The most suitable extraction, isolation and purification procedures of flavonols were fully described in this study. The identification of isolated flavonols (quercetin & kaempferol) was carried out using melting point (M.P.), Thin Layer chromatography (TLC), and infrared spectroscopy (IR).This study confirms the presence of quercetin and kaempferol in Ammi majus & an Ammi visnaga fruit, the percentage of quercetin was higher in Ammi visnaga than Ammi majus, while the percentage of kaempferol was higher in Ammi majus than Ammi visnaga. Key words : Ammi majus , Ammi visnaga , quercetin , kaempferol .